Aníbal Quijano: towards a new horizon of historical sense of a civilization of life - Ríos Burga, Jaime R. (2019)
The theoretical contribution of Aníbal Quijano to social thought, social theory and world, Latin American and Caribbean sociology theory is fertile and original. The present article tries to reconstruct some of his ideas in his last creative stage that converge in his preoccupation to build a new horizon of historical sense of a civilization of life. A creative contribution that in its continuity follows the Andean civilizational contributions of Guaman Poma and Mariátegui, posing today the challenge of continuing to enrich its meta-theoretical and theoretical sociological construction with new questions and answers by uniting what modernity / coloniality separated: the true, good and beautiful